Palpebral Non-Hodgkin Lymphoma with Non-specific Reactive Hepatitis - Pradana Zaky Romadhon; Bagus Aulia Mahdi; Ugroseno Yudho Bintoro (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
ABSTRACT Extranodal Non-Hodgkin Lymphoma (NHL) remains an odd issue and something to discuss. Clinical evidence and guidelines on the treatment have not yet been broadly published and accessible. Here, we present a case of a thirty-eight years old woman complaining of mass on both lower lids of the eyes. The CT Scan examination showed enhancing solid masses on right-sided and left-sided palpebra inferior that press bulb oculi, suspected as bilateral malignant masses of bilateral palpebra inferior. Laboratory data revealed the surge of liver function marker. The patient was eventually diagnosed with Non-Hodgkin Lymphoma (NHL) of palpebra inferior B cell type high-grade stadium II E. Although there are still ongoing research and development of definitive treatments, R-CHOP a regiment given to this patient has shown complete favorable result with dosage adjustment due to the surge of basal liver function. The regiment was considered safe since no adverse effects reportedKeywords: extranodal, lymphoma non-hodgkin, palpebra, liver function